Alumina ceramic membrane incorporated with graphene oxide frameworks for protein recovery / Noor Fauziyah Ishak - Noor Fauziyah , Ishak (2020)
Alumina ceramic membrane is undergoing rapid development and innovation for protein recovery process. However, the limitation of this membrane type is membrane fouling due to the deposition and adsorption of proteins on the surface and pore walls of the membranes. It is crucial to minimize membrane fouling by reducing interactions between protein and the membrane surface via surface modification technique. Thus, the main objective of this research is to develop an alumina membrane with enhanced antifouling property for protein recovery process. An alumina dope consisting of 57 wt.% alumina loading was used to fabricate two alumina membrane configurations; which are flat-sheet alumina (FSA) and hollow fibre alumina (HFA) membranes, via phase-inversion and sintering method. The FSA membrane was prepared through parametric study by optimizing the fabrication parameters which are the blade gap and sintering temperature. With the use of a blade gap of 1 mm and sintering temperature of 1500°C, it was possible to produce an FSA membrane with the highest flexure strength of 697 MPa and a pure water flux (PWF) of 1716 L/m2 .h and peak diameter for pore size distribution of 0.14μm. Meanwhile, the HFA membrane prepared for this study has a PWF of 242.63 ± 24 L/m2 .h, flexure strength of 156 ± 25MPa, contact angle of 29 ± 6°, surface roughness of 59.69nm and peak diameter for pore size distribution of 0.182μm. For the performance of protein recovery, FSA and HFA membranes have a low value of 35 ± 5% and 63.58 ± 0.5% respectively. In addition, the flux recovery rates (FRR) for FSA and HFA membranes were 25.32% and 63.37% respectively. Next, the surface of these membranes was further modified using graphene oxide frameworks (GOFs) as modifier agents to form a selective layer on alumina support. Three different concentrations of GOF(EDA) film was prepared for FSA membrane, and the lowest GO concentration of 5ppm which was 5GOF(EDA)/FSA composite membrane, had the highest PWF of 38.6 ± 1.1L/m2 .h. It also had a BSA recovery of 55 ± 6% at FRR of 46 ± 3% and the membrane pore size of 0.12 µm. In contrast, the HFA membrane had three composite membranes with different diamine monomers which are ethylenediamine (EDA), butylenediamide (BDA) and phenylenediamine (PDA). Among the composite membranes, the GOF(BDA)/HFA exhibited the highest PWF of 10 ± 0.6 L/m2 .h and flexure strength of 197.58 ± 12 MPa. For protein recovery, this composite membrane also exhibited the highest recovery rate among other modified membranes which are 98.40, 98.32, 95.82 and 95.65% for bovine serum albumin (BSA), egg albumin (EA), trypsin (TR) dan lysozyme (LSZ) protein respectively. Furthermore, the FRR and Rt result also suggest that GOF(BDA)/HFA composite membrane had better antifouling properties as it has the highest FRR and lowest total fouling ratio (Rt) of 94.86 % and 21.70 %, respectively for a total of 72h filtration time. As a conclusion, both surfaces modified with FSA and HFA membrane using GOF exhibited better performance in protein recovery application due to antifouling properties.